Experiences of symptom burden among young children born with esophageal atresia–tracheoesophageal fistula: a US focus group study - Michaela Dellenmark-Blom; John Bennett; Rosella Micalizzi; Lianne Cole; Kaylee Woods; Lauren Cardoni; Leah Frain; Abdimajid Mohamed; Jessica Yasuda; Peter Ngo; Anke Widenmann; Graham Slater; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Children born with esophageal atresia–tracheoesophageal fistula (EA–TEF) can suffer from aerodigestive morbidity that impairs their quality of life and can persist into adulthood. Ameliorating their symptom burden requires a thorough understanding of the symptom experiences that children have early in life. We aimed to explore parents’ experiences of their children’s aerodigestive symptom burden during the first years of life after being born with EA–TEF. This exploration also aimed to help determine whether a disease-specific measurement of symptom burden is needed. Method Five standardized focus groups (FGs) with 22 parents of children with EA–TEF aged 6 months–7 years treated at a US tertiary pediatric surgical center were used to explore the children’s symptom experiences. The FGs were audio-recorded, transcribed, content analyzed into what symptoms were expressed, together with their stated frequency, severity and relation to child distress. Results Twenty-two parents made 450 unique statements about their children’s aerodigestive symptom experiences. The respiratory symptoms (n = 170 statements, n = 21 parents) included the following unique symptom expressions; Breathing difficulties (n = 21), Breathing sounds (n = 6), Cough (n = 17), Mucus problems (n = 22), Prone to frequent or severe respiratory infections (n = 20) and Reduced physical capacity/strength (n = 8). The digestive symptoms (181 statements, n = 21 parents) encompassed symptom expressions of Acid reflux/heartburn (n = 7), Hiccups (n = 1), Nausea (n = 2), Reflux/food coming up (n = 10), Stomach problems (n = 4), Swallowing difficulties (n = 24) and Vomiting/throw-up (n = 6). The descriptions of respiratory and digestive symptom experiences included a variation of symptom frequency, severity and child distress. Furthermore, feeding difficulties (99 statements, n = 22 parents) included the children’s Food refusal (n = 8), Need for mealtime adjustment (n = 7), Selective/restrictive eating (n = 14) and Upset/stress with feeds (n = 10). Most parents (n = 20, 91%) described that their children had symptom experiences that spanned all three categories (respiratory and digestive symptoms, feeding difficulties). Conclusions Young children born with EA–TEF experience a significant symptom burden that can be reflected as a summative composite of the dimensions respiratory and digestive symptom frequency, severity and distress, in addition to feeding difficulties. This supports the need for a disease-specific measurement of symptom burden that is guided by the content and wording obtained directly from the parents’ descriptions to help establish its content validity.